Maastricht. Zwitsers vernuft in een achttiende-eeuwse grensstad - Beckers, Remco (Wereldsteden van de Lage Landen. Stadsgeschiedenis van Nederland en België, 2025)
Keywords: Ausländischer Arbeitnehmer; Maastricht; Migration; Schweiz; Stadt; Stuckateur

Grenzüberschreitende Daseinsvorsorge in der Euregio Maas-Rhein. Was kann die Euroregion Pro Europa Viadrina lernen? - Unfried, Martin (Grenzüberschreitende Daseinsvorsorge. Stand und Perspektiven in europäischen Verflechtungsräumen, 2025)
Abstract: „Die euregionalen Partner in der Euregio Maas-Rhein, am Dreiländereck Deutschland/Niederlande/Belgien, haben in den letzten Jahrzehnten viel Erfahrung gesammelt beim Aufbau von Netzwerken im Bereich der öffentlichen Dienstleistungen. Der Artikel stellt wesentliche Netzwerke vor, wobei ausführlicher eingegangen wird auf die Entwicklungen im Bereich der Notfallrettung und der Gesundheitsversorgung, des öffentlichen Nahverkehrs und der Wohnungsmarktpolitik.“
Keywords: Euregio Maas-Rhein; Medizinische Versorgung; Rettungswesen; Wohnungsmarkt; Wohnungspolitik; Öffentlicher Personennahverkehr

De bewaking van de Dodendraad in Limburg en de Antwerpse Kempen. Een blik achter de schermen - Vanbussel, Jef (Limburg. Het Oude Land van Loon, 2024)
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Kempenland; Militär

Maastrichtse industriëlen en het Belgische annexisme in de jaren 1918–1919 - Beaumont, Eddy de (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
Abstract: „During and immediately after the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. How did industrialists in the capital Maastricht respond to these Belgium goals? In this article, I explore the perspectives of an industrialist, a state detective and an economist in this matter. The industrialist was a fierce opponent of annexation, while the state detective was convinced that annexionists, those who were in favour of annexation, should mainly be found among major industrialists. The economist, on the other hand, did not rule out the possibility that some of Maastricht’s traders and industrialists would prefer a connection with Belgium. How did they come to these conclusions and to what extent did their considerations and other sources provide an answer to the research question of this article? Taking both gossip and facts into account, we may conclude that indeed there could have been traders and industrialists who supported the Belgian aspirations and preferred to join Belgium. However, the general claim that, in Maastricht especially, major industrialists were in favour of annexation lacks any factual evidence.“
Keywords: Annexion; Erster Weltkrieg; Industrie; Maastricht; Provinz Limburg (Niederlande); Widerstand

Het Maas-Scheldekanaal, een bron van conflicten - Borger, Guus J. (Het landschap beschreven. Historisch-geografische opstellen voor Hans Renes, 2021)
Keywords: Binnenschifffahrt; Kanal; Maas; Niederrhein-Gebiet; Rhein; Rhein-Maas-Gebiet; Schelde; Schifffahrtskanal

„Gemeinsame Ordnungen“ oder „Grenzen“ - Historiker und der Begriff des Rheinlandes vor dem Ersten Weltkrieg. Justus Hashagen (1877–1961) im Kontex - Mölich, Georg (Les pays de l'entre-deux. Übergangsräume - Grenzregionen - Konfliktzonen. Mit Beiträgen der Jahrestagung 2019 in Saarbrücken, 2021)
Keywords: Rheinland

Partnerschaft der kurzen Wege. Fünfzig Jahre Jumelage zwischen Wegberg, Echt (NL) und Maaseik (B) - Pietsch, Folkmar (Heimatkalender des Kreises Heinsberg, 2021)
Keywords: Echt (Provinz Limburg; Niederlande); Maaseik; Städtepartnerschaft; Wegberg

Border Management during the Eighty Years' War. Passports for Persons Crossing the New Habsburg-Dutch Border, 1568–1648 - Ridder, Bram de (Transregional territories. Crossing borders in the early modern Low Countries and beyond, 2020)
Keywords: Achtzigjähriger Krieg; Grenzpolizeiliche Kontrolle; Personalausweis

Vormen van regionaal bewustzijn en nationale identiteit in Belgisch- en Nederlands-Limburg 1866–1938 - Arijs, Karen (Verloren, 2017)
„In 1839 gingen Nederland en België uit elkaar. Sindsdien waren er twee provincies met de naam Limburg en de rivier de Maas werd een staatsgrens. Karen Arijs onderzoekt of zich na het ontstaan van de beide Limburgen een grensoverschrijdend regionaal bewustzijn heeft ontwikkeld. Vonden de bewoners aan weerskanten van de Maas dat zij meer met elkaar waren verbonden dan met andere Belgen/Vlamingen respectievelijk Nederlanders/rooms-katholieken? Voelden zij zich meer verbonden met hun streek (Groot-Limburg) dan met hun land? De vraag wordt uitgewerkt aan de hand van koninklijke bezoeken, herdenkingen, historische optochten en andere openbare feestelijkheden in Hasselt, Tongeren en Maastricht. De belangrijkste conclusie van het onderzoek is dat er van interregionaal bewustzijn geen sprake was. Het grensoverschrijdend regionalisme, dat gelooft in een tijdloze toestand van 'samen horen', is een hedendaags idee.“
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2017/08/06/file_4/7325428.pdf
Keywords: Hasselt (Albertkanal); Hochschulschrift; Maastricht; Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität; Tongern

Les habitants des pays d'Outre-Meuse et le paradoxe des frontière - Haye, Régis M. de la (Le Duché de Limbourg et les pays d'Outre-Meuse. Actes du colloque international tenu à Liège et à Maastricht les 23 et 24 mai 2016, 2017)
Keywords: Herzogtum Limburg

Les «Kinkenwegen» et «kinkenvoerders» du duché de Limbourg et des pays d'Outre-Meuse. Le transport des céréales et du charbon à l'aide de chevaux de bât dans la région transfrontalière d'Aix-la-Chapelle, Liège et Maastricht, aux XVIIIe et XIXe siècles - Paulissen, Maurice (Le Duché de Limbourg et les pays d'Outre-Meuse. Actes du colloque international tenu à Liège et à Maastricht les 23 et 24 mai 2016, 2017)
Keywords: Grenzverkehr; Herzogtum Limburg; Straße; Verkehr

Troebele betrekkingen. Grens-, scheepvaart- en waterstaatskwesties in de Nederlanden tot 1800 - Zijlmans, Roel (Verloren, 2017)
Aus der Verlagsmeldung: „Dit boek beschrijft de belangrijkste aspecten van de grensvorming tussen de Noordelijke en de Zuidelijke Nederlanden, van de Romeinse Tijd tot aan de negentiende eeuw. Onderdeel daarvan zijn bilaterale scheepvaart- en waterstaatskwesties. Ze worden behandeld vanuit de politieke geschiedenis, rechtsgeschiedenis en waterbouwkunde. Zijlmans besteedt aandacht aan de grote maar vrij onbekende strategische kanaalverbindingen en rivierverleggingen, die het Zuiden economisch en militair overwicht moesten verschaffen. Doorlopend richtpunt is de rechtsgeschiedenis van de doorvaart op grensoverschrijdende rivieren, zoals de Schelde. De 'sluiting' van deze rivier in de Tachtigjarige Oorlog brengt hij tot reële proporties terug. Ook prikt hij mythes door over het rivierenrecht. Het naschrift behandelt de argumentaties over het Schelderegime, speciaal de vermeende verplichting om de Westerschelde steeds aan te passen aan ontwikkelingen van de scheepvaart. Het gedegen bronnenonderzoek is verwerkt tot een eigenzinnig en goed leesbaar verhaal dat een nieuwe visie biedt op Belgisch-Nederlandse kwesties.“
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2017/05/24/file_6/7224946.pdf
Keywords: Hochschulschrift; Konflikt; Schelde; Schifffahrtskanal; Verwaltungsgrenze; Wasserbau

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Pierre Nothomb, het comité de politique nationale en de Belgische annexionistische campagne tijdens en na de Eerste Wereldoorlog - Waele, Maria de (Studies over De Sociaaleconomische Geschiedenis Van Limburg/Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2015)
Keywords: Annexion; Erster Weltkrieg; Nothomb; Pierre (1887–1966); Versailler Vertrag (1919)

„Die aan ‘t verleden raakt kan altijd tooveren“. Twee standbeelden voor Hendrik van Veldeke. Lokaal initiatief en Limburgse identiteit - Arijs, Karen (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2014)
Keywords: Hasselt (Albertkanal); Kollektives Gedächtnis; Maastricht; Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Mijnbouw en grensarbeid in het Nederlands-Belgisch-Duitse grensgebied, 1900–1973. Een overzicht - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2014)
Keywords: Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Hoogspanning aan de Belgisch-Nederlandse grens. De Eerste Wereldoorlog aan de rijksgrens met Baarle - Janssen, Herman (Heemkundekring Amalia van Solms Baarle-Hertog-Nassau, 2013)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2014/01/26/file_2/5465730.pdf
Keywords: Baarle-Hertog; Baarle-Nassau; Elektrozaun; Erster Weltkrieg

Living on the edge. Comparative research on German, Belgian and Dutch border towns at war (1914–1919) - Liemann, Bernhard (Grenzfälle: Transfer und Konflikt zwischen Deutschland, Belgien und den Niederlanden im 20. Jahrhundert, 2013)
Keywords: Erster Weltkrieg; Eupen; Grenzstadt; Roermond; Tongern

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

De grens. Langs de randen van Nederland - Witt, Enno de (Athenaeum-Polak & Van Gennep, 2013)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2013/06/05/file_2/5145212.pdf

Liefde met en zonder grenzen. De geografische horizon van huwelijkspartners in Limburg in de negentiende en vroege twintigste eeuw - Ekamper, Peter; Poppel, Frank van (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Binationale Ehe; Binationales Ehepaar; Ehepaar; Kulturkontakt; Provinz Limburg (Niederlande)

Small towns in the Great War. German, Belgian and Dutch perspectives from the border region compared (1914–1919) - Liemann, Bernhard (Internationale Archivsymposien in Ede (NL) (2010) und Lüttich (B) (2011) – Annalen, 2012)
Keywords: Erster Weltkrieg; Eupen; Grenzstadt; Roermond; Tongern

Grenz-Controle, Grens-Kontrolle. Aachen, Eupen, Maastricht - oral histories - Boogard, Jac van den; Clemens, Luise; Heinen, Armin; Jantsch, Johanna; Ruland, Herbert; Schleinzer, Anika (Gardez!-Verlag, 2008)
Inhaltsverzeichnis: https://d-nb.info/989105156/04
Keywords: Alltag; Dreiländereck; Grenzgebiet; Rhein-Maas-Gebiet

Goed betaald? Mijnwerkerslonen en arbeidsmarkt in het Nederlands-Duits-Belgische grensgebied in de achttiende en negentiende eeuw - Gales, Ben A. (Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2008)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Inleiding. Arbeidsmigranten en grensarbeiders. Vergelijkende perspectieven op de mijnarbeidsmarkten in het Belgisch-Duits-Nederlandse grensgebied in de twintigste eeuw - Knotter, Ad (TSEG - The Low Countries Journal of Social and Economic History, 2008)

Limburg bestaat niet. Paradox van een sterke identiteit - Knotter, Ad (Bijdragen en mededelingen betreffende de geschiedenis der Nederlanden (BMGN), 2008)
Keywords: Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Boten op de Maas en een molenaarskar met bellen. Smokkelaars en douaniers aan de grens van napoleontisch Frankrijk - Welten, Joost (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2008)
Keywords: Maas; Schmuggel

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

De bunkers van de grensstelling langs de Limburgse kanalen (1934–1940) - Janssen, Erik (Uitg. De Krijger, 2005)
Keywords: Befestigung; Kanal; Militär; Zweiter Weltkrieg

Euregio Carolus Magnus. Grenzen in Fluss. Wissenswertes, Historisches, Kurioses rund um das Städtedreieck Maastricht - Aachen - Lüttich - Kamermans, Johanna (Verlag Mainz, 2004)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2024/08/24/file_11/9585690.pdf
Keywords: Aachen (Region); Euregio Maas-Rhein; Lüttich; Maastricht

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Grenzen-Los, Grenzen-Loos, Sans-Frontières - zu Gegenwart und Perspektiven grenzüberschreitender politisch-historischer Bildung am Dreiländereck Belgien, Deutschland, Niederlande - Ruland, Herbert (Grenzen überschreiten - Netze bilden. Nutzen und Kosten für die Erwachsenenbildung. Dokumentation der 45. Salzburger Gespräche für Leiterinnen und Leiter in der Erwachsenenbildung / Pädagogische Arbeits- und Forschungsstelle des Verbandes Österreichischer Volkshochschulen, 2003)
Keywords: Dreiländereck; Politische Bildung

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Hoheitsrechte und Besitzungen Karls V. im Rheinland. Von der Mosel bis zur Nordsee. Eine Beschreibung der östlichen Grenze der Erbniederlande - Vilar Sánchez, Juan Antonio (Karl V. 1500–1558. Neue Perspektiven seiner Herrschaft in Europa und Übersee, 2002)
Keywords: Herrschaft; Karl V. (Heiliges Römisches Reich; Kaiser) (1500–1558); Rheinland

Paradoxen van de grens. Ongelijke ontwikkeling, grensoverschrijdende mobiliteit en de vergelijkende geschiedenis van de Euregio Maas-Rijn - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg - Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2001)
Keywords: Euregio Maas-Rhein; Grenzverkehr

Entstehung und Verfestigung der Grenze zwischen den südlichen und den nördlichen Niederlanden. Politische Kontingenz und kulturelles Konstrukt - Mörke, Olaf (Frieden und Krieg in der Frühen Neuzeit. Die europäische Staatenordnung und die außereuropäische Welt, 2001)
Keywords: Achtzigjähriger Krieg; Staatsgrenze

„Das Loch im Westen“ - Ein Schmuggelparadies - Trees, Wolfgang (Deutschland - Niederlande. Heiter bis wolkig. [Begleitbuch zur Ausstellung im Haus der Geschichte der Bundesrepublik Deutschland, Bonn, 22. November 2000 bis 16. April 2001 und im Rijksmuseum, Amsterdam, 26. Mai bis 16. September 2001], 2000)
Keywords: Aachen (Region); Herzogenrath; Kerkrade; Schmuggel; Vaals

Kroniek van een Dorp in Oorlog. Neerpelt 1914–1918. Het dagelijks leven, de spionage en de elektrische draadversperring aan de Belgisch-Nederlandse grens tijdens de Eerste Wereldoorlog - Vanneste, Alex (Universitas, 1998)
Keywords: Elektrozaun; Erster Weltkrieg; Neerpelt

Wisselende perspectieven van grensligging in de geschiedenis van de euregio Maas-Rijn - Jansen, Johannes C. G. M. (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 1997)
Keywords: Euregio Maas-Rhein; Grenzüberschreitende Kooperation

Bestuurlijke vernieuwing in grensgebieden. Intergemeentelijke grensoverschrijdende samenwerking in het Nederlands-Belgisch grensgebied - Kessen, Antoine Alcide Louis Guillaume Marie (1992)
Keywords: Grenzüberschreitende Kooperation

Smokkelen in Brabant. Een grensgeschiedenis 1830–1970 - Spapens, Paul; Oirschot, Anton van (De Kempenpers, 1988)
Keywords: Nordbrabant; Schmuggel

Een staatsgrens door de Nederlanden - Bieze, J.W. (Nationaal Museum van Douane en Accijnzen, 1986)
Keywords: Staatsgrenze; Zollgrenze

Perikelen rond grenspaal no. 176 - Bieze, J.W. (De Rosdoek, 1986)
Keywords: Grenzstein

De Zuidgrens van ons koninkrijk - Bieze, J.W. (Stichting Belastingmuseum Prof. dr. Van der Poel, 1985)
Keywords: Staatsgrenze; Zollgrenze

De rijksgrens tussen België en Nederland als taalgrens. Lezingen, gehouden voor de Dialectencommissie der Koninklijke Nederlandse Akademie van Wetenschappen op 3 januari 1957 - Weijnen, Antonius A.; Coetsem, Frans van (Noord-Hollandsche Uitg. Maatschappij, 1957)
Keywords: Niederländisch; Sprachgrenze; Staatsgrenze